PENGEMBANGAN MEDIA MEMAHAMI KALIMAT (MAMAT) BERBASIS ARTICULATE STORYLINE UNTUK SISWA KELAS III PADA MUATAN PELAJARAN BAHASA INDONESIA - Lilis Maulidiah Astuti; Treny Hera; Sonia Anisah Utami (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop MAMAT learning media based on articulate storyline in learning Indonesian Language Theme 5 Subtheme 1 Lesson 1 Effective Sentence Material that is valid and practical. The type of research used in this study is research and development (R&D) referring to the ADDIE model with stages, namely Analysis, Design, Development, Implementation, Evaluation. Based on expert tests from validators covering three aspects, namely media, language, and materials, the results of this study obtained an average percentage of 88.2% with the category "very valid" then supported by the results of direct student trials (one to one) and obtained a percentage of 94% with the category "very practical", the last trial was a trial in small groups (small group) by obtaining an average percentage of 97.8% with the category "very practical". So that the development of this MAMAT media is valid and practical for use in broader learning. Keywords: Development, MAMAT, Articulate Storyline, Indonesian